The relationship between board of director's characteristics and industrial firms financial performance listed at Amman Stock Exchange - Qadorah, Almontaser Abdallah Mohammad (2016)
The purpose of this study is to empirically examine the relationship between board size, CEO duality, independence of the board of director’s, frequency of board meeting and firm financial performance. About, 64 industrial listed firms are chosen from Amman Stock Exchange for the year 2013. Multiple regressions analysis is utilised in this study in order to achieve the research objectives. The findings show that board size, CEO duality, independence of the board of director's and frequency of board meeting have a relationship with firm financial performance. The findings also show that board size has a positive relationship with firm financial performance, and CEO duality has a negative relationship with firm financial performance. Moreover, independence of the board of directors has a positive relationship with firm financial performance. Eventually, the frequency of board meeting has no relationship with firm financial performance. It should be noted that the findings established in this study could be useful to regulators, especially the industrial firms listed in Amman Stock Exchange (ASE), Jordanian Securities Commission (JSC) and Jordan Investment Commission (JIC) to improve Corporate Governance (CG) practices. This study proposes that listed firm should put more emphasis on enhancing the role and the quality of the board of directors, as they are involved in the decisions that improve firm financial performance.